Comparative Study of CO₂ Laser and Curettage-Electrodesiccation for Superficial Basal Cell Carcinoma Treatment: A Focus on Cosmetic Results - Pelle Kahr Nilsson; Ulrik Knap; Rasa Laurinaviciene; Sebastian Vigand Svendsen; Tine Vestergaard (Dermatology Practical & Conceptual)
Introduction: Basal cell carcinoma (BCC) is the most common type of skin cancer worldwide, and the incidence is rising. While surgical excision remains the gold standard, it can be time-consuming and resource-intensive. Therefore, there is a growing need for simpler and more cost-effective treatment options for low-risk tumors.